2011
DOI: 10.1007/s00134-011-2226-0
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure and its surrogates

Abstract: Intracranial hypertension [intracranial pressure (ICP) [20 mmHg] is a life-threatening complication seen in a significant proportion of patients following severe traumatic and nontraumatic brain insults [1][2][3]. Sustained elevations in ICP generally signal secondary injury processes such as cerebral edema, hemorrhage, hydrocephalus and ischemia, and as a consequence the management of ICP has become a keystone in neurocritical care. Especially in unresponsive patients when the diagnostic yield of physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The results of the study were consistent with the clinical studies [5, 17] but not consistent with case report [19]. The possible justification is that in physiological parameters may affect pulsatility index [17] while intracranial pressure is independent parameter [20]. Even, intracranial pressure is a dynamic dimension that changes rapidly with time [7] and it is unclear whether or how pulsatility index would change.…”
Section: Discussionsupporting
confidence: 69%
“…The results of the study were consistent with the clinical studies [5, 17] but not consistent with case report [19]. The possible justification is that in physiological parameters may affect pulsatility index [17] while intracranial pressure is independent parameter [20]. Even, intracranial pressure is a dynamic dimension that changes rapidly with time [7] and it is unclear whether or how pulsatility index would change.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, previous studies demonstrated a good intra- and inter-observer reliability of the measurement of ONSD by ultrasonography [ 12 , 13 ]. It has been suggested as an indicator of intracranial hypertension in recent years [ 10 , 14 19 ]. However, there is still no unified standard threshold of enlarged ONSD to determine intracranial hypertension, which varies from 5.0 mm to 5.9 mm [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although elevated ICP can be detected by computed tomography or magnetic resonance imaging, these techniques are expensive, time-consuming and requiring patient’s transportation. In recent years, measurement of optic nerve sheath diameter (ONSD) by ultrasonography has been developed and suggested as a possible indicator of intracranial hypertension [ 10 ]. The optic nerve sheath is a membrane covering the optic nerve behind the eye, and is continuous with the dura mater over the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, prediction and monitoring of ICP are recommended in stroke and in cases suspicious of having intracranial hypertension 7 . Recent studies show that measurement of optic nerve sheath diameter (ONSD) (a membrane continuous with the dura mater) by ultrasound (US), is indirectly an indicator of ICP 8 …”
Section: Introductionmentioning
confidence: 99%